Resting Body Temperature and Long-Term Survival in Older Adults at a Mental Health Center: Cross-Sectional and Longitudinal Data - Chmielewski, Piotr Paweł; Strzelec, Bartłomiej; Data, Krzysztof; Chmielowiec, Krzysztof; Mozdziak, Paul; Kempisty, Bartosz (Journal of clinical medicine, 2025)
Background/Objectives: Elevated body temperature is a well-established biomarker of infection, increased disease risk, and adverse health outcomes. However, the relationship between resting body temperature and long-term survival in older individuals is complex. Emerging evidence suggests that higher basal body temperature is associated with reduced survival and accelerated aging in non-obese older adults. This study aimed to compare body temperatures across different age groups in hospitalized older adults. Methods: Data were retrospectively collected from 367 physically healthy residents of a mental health center. Longitudinal data from 142 individuals (68 men and 74 women), aged 45 to 70 years and monitored continuously over 25 years, were compared with cross-sectional data from 225 individuals (113 men and 112 women) who underwent periodic clinical examinations with temperature measurements. The cross-sectional sample was stratified into four survival categories. Resting oral temperatures were measured under clinical conditions to ensure protocol consistency. Age-related changes in both sexes were evaluated using standard regression analysis, Student's t-tests, ANOVA, and Generalized Linear Models. Results: Longitudinal analysis revealed an increase in body temperature with age among women, while cross-sectional analysis showed that long-lived residents generally had lower body temperatures compared to their shorter-lived counterparts. Conclusions: These findings support the hypothesis that lower lifetime steady-state body temperature is associated with greater longevity in physically healthy older adults. However, further research is needed to determine whether the lower body temperature observed in long-lived individuals is linked to specific health advantages, such as enhanced immune function, absence of detrimental factors or diseases, or a reduced metabolic rate potentially influenced by caloric restriction.
Keywords: biomarkers; thermoregulation; body temperature; survival; health outcomes; longevity